Analysis of the Causes and Effects of Social Exclusion in the Assessment of Cooperative Bank Customers – Research Report - Szewczyk-Jarocka, Mariola (Acta Universitatis Lodziensis. Folia Oeconomica, 2025)
The main goal of the considerations presented in the article was analysis the causes and effects of social exclusion according to the opinions of customers of cooperative banks. Survey research according to the interview questionnaire was conducted in 2023 on an sample of 1502 customers of cooperative banks. The research sample was of a quota-targeted nature. The quantitative survey of cooperative bank customers was carried out according to the Mixed Mode Design procedure. Research results indicate that income, socio-professional status and age mainly cause social exclusion. However, according to the respondents, poverty, unemployment and disability mainly contribute to social exclusion. In turn, the effect of social exclusion, according to respondents, is the development of pathological social phenomena, fewer opportunities and a worse economic situation, and the loss of competences enabling a return to the labor market. Social exclusion is phenomenon that has many causes. The novelty of the study is the fact that it was conducted on a sample of customers of cooperative banks, because this group often declares low net income and is socially, financially and digitally excluded.